Pengaruh penghargaan finansial, lingkungan keluarga, dan pertimbangan pasar kerja terhadap minat mahasiswa berkarir menjadi akuntan - Yati, Yati; Br.Purba, Neni Marlina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The motivation for this study is these questions of imbalance in the number of students majoring in accounting with the number of certified public accountants in Batam City. The purpose of this research is to develop and anticipate problems related to the influence of the independent variables in the research on the dependent variable in the research. This study uses primary data with quantitative methods, namely by conducting a direct survey of the research population with the qualifications determined by the researcher. Then the survey results that have been obtained are processed using the SPSS version 20.0 application to generate useful information for drawing research conclusions and supporting/rejecting the theoretical basis that underlies this research. The results obtained from this study are that the independent research variables (financial rewards, family environment, and labor market considerations) partially and simultaneously influence students' interest in careers to become Certified Public Accountants. The conclusion in this study is that the researcher rejects h0 which states that the independent variables have no effect on the dependent variable, and accepts H1, H2, H3, and H4 which state that Independent variables partially or completely affect the dependent variable.